Description and identification of tuna larvae based on genetic and morphological analysis. Issue 1 (December 2020) - Romdon, A; Sembiring, A; Pertiwi, N P D; Malik, M D A; Pay, L; Hehuwat, Y; Satrioajie, W N
Abstract: Biological information of tuna larvae is essential for understanding spawning ground and time. However, morphological identification of fish larvae is difficult and questionable. Meanwhile, genetic identification is useful and helpful to confirm the morphological identification result. This study purpose is to confirm a morphological identification result with genetic identification and determine the tuna species exactly. Specimens were obtained from a survey conducted in the Banda Sea in October 2018. Samples were collected by a bongo net towed obliquely. The result of morphological identification is showed that the larvae having 37 to 42 myomeres, preopercular spine developed, moderate in-depth, moderate to large head and eyes identified as Thunnini larvae. The morphological result is supported by the genetic result, even though the larvae are not from the genus of Thunnus . The samples were identified as Katsuwonus pelamis, Euthynnus affinis, and Petenia splendida . The intraspecific pairwise genetic distance for each species of K. pelamis, E. affinis, and P. splendida is 4.4 %; 0.5 %; and 22.3%, respectively. Meanwhile, the average pairwise genetic distance between the three species ranges from 16.2% to 33.3%.